2018
DOI: 10.3390/ijms19010246
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of Metal Oxide Nanoparticles on Cell Viability and Activation of MAP Kinases and NFκB

Abstract: In recent years, there has been an increase in the production of several types of nanoparticles (Nps) for different purposes. Several studies have been performed to analyse the toxicity induced by some of these individual Nps, but data are scarce on the potential hazards or beneficial effects induced by a range of nanomaterials in the same environment. The purpose of the study described here was to evaluate the toxicological effects induced by in vitro exposure of human cells to ZnO Nps in combination with dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…For instance, Opeoluwa M. Ogunsuyi et al [28] found that both NPs and their mixture apparently altered sperm motility, reduced sperm numbers, and increased abnormalities, while their mixture induced more sperm abnormalities than either TiO 2 NPs or ZnO NPs alone. In addition, in human Jurkat cells, TiO 2 NPs also increased the cytotoxicity of ZnO NPs but reduced the phosphorylation of some signaling proteins, thus suggesting that the synergistic toxic effect may be related to intracellular activation routes [29]. However, some studies have demonstrated the antagonistic toxicity between ZnO NPs and TiO 2 NPs, including our conclusions.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…For instance, Opeoluwa M. Ogunsuyi et al [28] found that both NPs and their mixture apparently altered sperm motility, reduced sperm numbers, and increased abnormalities, while their mixture induced more sperm abnormalities than either TiO 2 NPs or ZnO NPs alone. In addition, in human Jurkat cells, TiO 2 NPs also increased the cytotoxicity of ZnO NPs but reduced the phosphorylation of some signaling proteins, thus suggesting that the synergistic toxic effect may be related to intracellular activation routes [29]. However, some studies have demonstrated the antagonistic toxicity between ZnO NPs and TiO 2 NPs, including our conclusions.…”
Section: Discussionsupporting
confidence: 51%
“…Conversely, Ogunsuyi et al found that the mixture of these two NPs resulted in a significant synergistic effect on mice testis injury; the combination significantly reduced sperm motility and sperm number and markedly increased sperm abnormalities and aberrations compared with exposure to each NP type alone [28]. In addition, for human Jurkat cells, TiO 2 NPs also increased the cytotoxicity of ZnO NPs and reduced the phosphorylation of the signaling proteins [29]. As can be seen, the health hazard induced by co-exposure to different NPs has gradually attracted people's attention.…”
Section: Introductionmentioning
confidence: 99%
“… 22 The unique properties and interactions between nanomaterials with biological system are essential. 23,24 Cell line toxicity of human cell lines by using several synthesized metal oxides are more attractive in understanding the relationship between nanoparticle–cell interaction as well as in biocompatibility studies. 25,26 Furthermore, biocompatibility must be conducted with particular focus on the environment in which the nanomaterial will be placed in.…”
Section: Introductionmentioning
confidence: 99%